Connectivity Patterns of Subthalamic Stimulation Influence Pain Outcomes in Parkinson's Disease - Cury, Rubens Gisbert; Teixeira, Manoel Jacobsen; Galhardoni, Ricardo; Silva, Valquiria; Iglesio, Ricardo; França, Carina; Arnaut, Débora; Fonoff, Erich Talamoni; Barbosa, Egberto Reis; Ciampi de Andrade, Daniel (Frontiers in Neurology, 2020)
Background: Pain is highly prevalent in Parkinson’s disease and is associated with significant reduction in health-related quality of life. Subthalamic deep brain stimulation can produce significant pain relief in a subset of patients after surgery. However, the mechanism by which deep brain stimulation modulates sensory function in Parkinson’s disease remains uncertain. Objective: To describe the motor and pain outcomes of deep brain stimulation applied to a series of patients with Parkinson’s disease and to determine whether the structural connectivity between the volume of tissue activated and different regions of the brain were associated with the changes of these outcomes after surgery. Methods: Data from a long-term prospective cohort of 32 Parkinson’s disease patients with subthalamic stimulation were combined with available human connectome to identify connections consistently associated with clinical improvement (Unified Parkinson Disease Rating Scale), pain intensity, and experimental cold pain threshold after surgery. Results: The connectivity between the volume of tissue activated and a distributed network of sensory brain regions (prefrontal, insular and cingulate cortex, and post-central gyrus) was inversely correlated with pain intensity and cold pain threshold improvement after surgery (p<0.01). The connectivity strength with the supplementary motor area positively correlated with motor and pain threshold improvement (p<0.05). Conclusions: This data suggests that the pattern of the connectivity between the region stimulated and specific brain cortical area might be responsible, in part, for the successful control of motor and pain symptoms by subthalamic deep brain stimulation in Parkinson’s disease.